2020
DOI: 10.1101/2020.03.22.20041145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global transmission network of SARS-CoV-2: from outbreak to pandemic

Abstract: Background. The COVID-19 pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is straining health systems around the world. Although the Chinese government implemented a number of severe restrictions on people's movement in an attempt to contain its local and international spread, the virus had already reached many areas of the world in part due to its potent transmissibility and the fact that a substantial fraction of infected individuals develop little or no symptoms at all. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…Heterogeneity is the hallmark of the transmission pattern of SARS-CoV-2, as inferred from global molecular epidemiologic studies. [18] Its propagation varies by the rate and extent of secondary transmission in the population, which is in turn dependent on the settings of virus exposure. Our results reported, for the first time, the association between exposure settings and the propagation of transmission clusters using real world surveillance and contact tracing data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneity is the hallmark of the transmission pattern of SARS-CoV-2, as inferred from global molecular epidemiologic studies. [18] Its propagation varies by the rate and extent of secondary transmission in the population, which is in turn dependent on the settings of virus exposure. Our results reported, for the first time, the association between exposure settings and the propagation of transmission clusters using real world surveillance and contact tracing data.…”
Section: Discussionmentioning
confidence: 99%
“…With a daily increase of over 0·2 million new cases, the ultimate toll of the pandemic may surpass many of the previous influenza pandemics. Amidst the widespread dissemination of COVID-19, marked heterogeneity of SARS-CoV-2’s transmission pattern is noted, [1] as has been described for the related virus causing SARS over a decade ago [2] . Modelling studies suggested the phenomenon of overdispersion, with 80% of the secondary transmission caused by a very small fraction of proportion of SARS-CoV-2 infected patients, [3] which explains the characteristics of outbreaks attributed to a single patient exposure, [4 , 5] or inferred from some big clusters as reported in South Korea [6] and Germany [7] .…”
Section: Introductionmentioning
confidence: 91%
“…The virus was later designated as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) based on taxonomic and genetic relationship with the previously identified SARS-CoV virus 4 . It’s high rate of transmissibility 5,6 allowed the virus to achieve global transmission rapidly 7,8 . The World Health Organization (WHO) announced COVID-19 as a pandemic on March 11, 2020 9 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 By the time China was the epicenter of this pandemic, a stringent framework for maintaining the distribution of these people had been placed in place, whether at local or international level, the virus had gained ground in many countries around the world, Partly because of its strong transmissibility, and also because a small fraction of infected persons experience little to no symptoms. 3 This global spread suggests a clear and actual understanding of this pathogen's dynamic properties, through modeling, adapting a phylogeographic method that allows for joint estimation of phylogeny and epidemiological parameters of interest. 4 By applying this discipline in this research, which is the most recent field of phylodynamics, 5 we can map the current SARS-CoV-2 migration scenario, between and within the three countries selected in this research (China [Shanghai], Italy, Spain), that we assume reflects what is happening around the world.…”
Section: Introductionmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic (2019) has placed health systems around the world on high alert, many governments have declared a strengthening of measures at their borders to prevent this virus from spreading 1,2 . By the time China was the epicenter of this pandemic, a stringent framework for maintaining the distribution of these people had been placed in place, whether at local or international level, the virus had gained ground in many countries around the world, Partly because of its strong transmissibility, and also because a small fraction of infected persons experience little to no symptoms 3 . This global spread suggests a clear and actual understanding of this pathogen's dynamic properties, through modeling, adapting a phylogeographic method that allows for joint estimation of phylogeny and epidemiological parameters of interest 4 .…”
Section: Introductionmentioning
confidence: 99%